1992
DOI: 10.1161/01.cir.86.2.699
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and cardiovascular disease. A position paper from the Council on Cardiopulmonary and Critical Care, American Heart Association.

Abstract: Although the number of cardiovascular deaths associated with environmental tobacco smoke cannot be predicted with absolute certainty, the available evidence indicates that environmental tobacco smoke increases the risk of heart disease. The effects of environmental tobacco smoke on cardiovascular function, platelet function, neutrophil function, and plaque formation are the probable mechanisms leading to heart disease. The risk of death due to heart disease is increased by about 30% among those exposed to envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 18 publications
0
97
0
3
Order By: Relevance
“…TSP is responsible for the preventable morbidity and mortality of hundreds of thousands of nonsmokers worldwide ( ( Glantz & Parmley, 1995 ;Law, Morris, & Wald, 1997 ;Taylor, Johnson, & Kazemi, 1992 ). Recently, a review of the epidemiological evidence concluded that TSP was associated with a signifi cant increase in breast cancer among premenopausal women ( California Environmental Protection Agency, Air Resources Board, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSP is responsible for the preventable morbidity and mortality of hundreds of thousands of nonsmokers worldwide ( ( Glantz & Parmley, 1995 ;Law, Morris, & Wald, 1997 ;Taylor, Johnson, & Kazemi, 1992 ). Recently, a review of the epidemiological evidence concluded that TSP was associated with a signifi cant increase in breast cancer among premenopausal women ( California Environmental Protection Agency, Air Resources Board, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…TSP is responsible for the preventable morbidity and mortality of hundreds of thousands of nonsmokers worldwide ( California Environmental Protection Agency, Air Resources Board, 2005 ;Fellows, Trosclair, Adams, & Rivera, 2002 ;Jamrozik, 2005 ;Klerman, 2004 ;National Cancer Institute, 1999 Kirkbride, & Mao, 1987 ;Woodward, Hill, & Blakey, 2004 ). TSP has been found to be a cause of lung cancer ( National Research Council, 1986 ; U.S. Department of Health and Human Services [USDHHS], 1986 ) and heart disease ( Glantz & Parmley, 1995 ;Law, Morris, & Wald, 1997 ;Taylor, Johnson, & Kazemi, 1992 ). Recently, a review of the epidemiological evidence concluded that TSP was associated with a signifi cant increase in breast cancer among premenopausal women ( California Environmental Protection Agency, Air Resources Board, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies demonstrate an increase in coronary artery disease (CAD) events and mortality with exposure to SHS. [1][2][3][4][5][6][7] Pooled analysis of the best-controlled studies of SHS suggests that SHS results in a relative risk of dying from heart disease as high as 1.7 (95% CI, 1.3 to 2.3). 2,4 The estimated cardiac mortality in the United States from SHS exposure is 53 000 deaths per year, [1][2][3][4] primarily from cardiovascular effects.…”
mentioning
confidence: 99%
“…Estas crianças têm uma maior incidência de doenças das vias aéreas inferiores, nomeadamente pneumonias, bronquiolites e bronquites, nos dois primeiros anos de vida. Também os sintomas respiratórios são mais frequentes entre os filhos de fumadores (43,44) .…”
Section: Poluentesunclassified